Pengaruh Inovasi Produk, Brand Image, Harga dan Sertifikasi Halal Terhadap Keputusan Pembelian Keripik Kulit Kebab Misscrip di Surabaya - Fitriyah, Sa'adatul; Tanuwijaya, Haryanto; Suhandiah, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to examine how consumer decisions to buy Misscrip brand kebab skin chips in Surabaya are influenced by price, halal certification, brand image, and product innovation. Using a quantitative methodology, the study gathers data via an online survey. There are 114 respondents in the sample who are above 17 and live in Surabaya. A five-point Likert scale was employed in the survey to gauge respondents' opinions. With the aid of SmartPLS software 4.1.0.9, data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study found that the four independent factors—price, halal certification, brand image, and product innovation—had a significant and favorable impact on consumers' decisions to buy. Brand image is the factor that influences purchases the most out of all of these. This research suggests that strengthening product innovation, developing a favorable brand image, setting competitive prices, and ensuring that products have halal certification are all crucial to making MSME products like Misscrip more competitive.